2005
DOI: 10.1111/j.1523-5378.2005.00356.x
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Possible Relation Between Atrophic Gastritis and Premature Atherosclerosis?

Abstract: Our results showed that atrophic gastritis may cause hyperhomocysteinemia, which is an independent risk factor for atherosclerosis and cardiovascular diseases. However, when compared with controls, carotid intima-media thickness of the atrophic gastritis patients was found to be higher but did not reach statistically significant levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…Moreover, arterial stiffness advanced in accordance with the severity of AG. This correlation between AG and arterial stiffness has been reported in a previous study, in which carotid intima-media thickness was greater in subjects with atrophic gastritis 24) ; however, no report has shown the relation of AG and arterial stiffness evaluated by baPWV or CAVI.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Moreover, arterial stiffness advanced in accordance with the severity of AG. This correlation between AG and arterial stiffness has been reported in a previous study, in which carotid intima-media thickness was greater in subjects with atrophic gastritis 24) ; however, no report has shown the relation of AG and arterial stiffness evaluated by baPWV or CAVI.…”
Section: Discussionmentioning
confidence: 66%
“…For more accurate diagnosis, HP status and AG should be determined by endoscopy and biopsy. Fourth, we did not measure lipoprotein-a 28) , vitamin B12 24) , fibrinogen, and cytokine levels 27) , all of which have been reported to be related to arterial stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies demonstrated an association between H. pylori infection and hyperhomocysteinemia 1-4, while the other studies did not. 15, 16, 21-23.…”
Section: Discussionmentioning
confidence: 98%
“…Hyperhomocysteinemia is a well-established independent risk factor for the development of atherosclerosis-related diseases since it causes vascular endothelial damage [45]. Several studies have suggested an association between H. pylori-related atrophic gastritis and hyperhomocysteinemia [27,28,46,47]. Therefore, H. pylori induced hyperhomocysteinemia may be one of the causal mechanisms underlying the reported association between infection and overt atherosclerotic disorders.…”
Section: H Pylori and Ironmentioning
confidence: 95%